P160 The Role Of Specialist Palliative Care Services In The Management Of Patients With Pulmonary Arterial Hypertension; A Review Of Current Practice. (10th November 2014) - Woolcock, SC; De Soyza, J; Crackett, R; Day, M; Fisher, AJ; Lordan, J; MacGowan, G; Corris, PA
Abstract : Introduction and objectives: Pulmonary Arterial Hypertension (PAH) is a severe, progressive condition characterised by increased pulmonary vascular resistance, right ventricular failure and death. Survival is strongly linked to functional class with patients persisting in WHO class IV surviving less than one year. Such patients commonly require repeated hospital admissions with intractable symptoms due to right heart failure. Although specialist palliative care involvement is recommended in current guidelines for the management of PAH, no formal recommendations exist presently to guide clinicians on timing of referral. The aim of this study was to outline current practice in this area and define the potential workload and role of specialist palliative care services. Methods: Data was collected retrospectively for all patients within our national PAH service who died over a one year period (June 2013–June 2014). We specifically looked at timing of referral and involvement of palliative care specialists, WHO functional class, clinical course prior to death and prognostic indicators of deterioration. Suitable patients were identified from the PAH and palliative care databases. Patient notes were reviewed to identify WHO class, clinical course prior to death and documented evidence of specialist palliative care involvement. Results: 31 patients were identified; (14 male, 17 female; 19 (61%) WHO IV, 9 (29%) WHO III, 3 (10%) WHO II). Only 11 (35%) had documented evidence of specialist palliative care involvement. 7 (22%) received input whilst in hospital, 4 (13%) in the community. Conclusions: The majority of our patients did not receive specialist palliative care support during the final stages of their disease. Whilst the majority (61%) of patients were functional class IV prior to death, 39% were functional class II or III. Progressive deterioration and increased burden of symptoms over time preceding death were commonly noted. Whilst the specialist PAH nurses and clinicians offer palliative care and support, our data suggests that a review of the timing, organisation and documentation of referral to specialist palliative care services requires consideration.